2010
DOI: 10.3844/jcssp.2010.29.35
|View full text |Cite
|
Sign up to set email alerts
|

Attack of Against Simplified Data Encryption Standard Cipher System Using Neural Networks

Abstract: Problem statement: The problem in cryptanalysis can be described as an unknown and the neural networks are ideal tools for black-box system identification. In this study, a mathematical black-box model is developed and system identification techniques are combined with adaptive system techniques, to construct the Neuro-Identifier. Approach: The Neuro-Identifier was discussed as a black-box model to attack the target cipher systems. Results: In this study this model is a new addition in cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It requires only an 8-bit block, whereas the original DES requires 64 bits, which amounts to an eight-fold simplification. Alallayah et al [28] propose a new complementary model discussed in the block cryptosystem (SDES) approach. The neural recognition model is constructed to achieve two goals.…”
Section: Sdes In Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires only an 8-bit block, whereas the original DES requires 64 bits, which amounts to an eight-fold simplification. Alallayah et al [28] propose a new complementary model discussed in the block cryptosystem (SDES) approach. The neural recognition model is constructed to achieve two goals.…”
Section: Sdes In Neural Networkmentioning
confidence: 99%
“…The network is an ideal tool for identifying black box systems. Alallayah et al [29] discuss the simplified DES (SDES) block encryption system. The neural recognition model was constructed to achieve two objectives.…”
Section: Sdes In Neural Networkmentioning
confidence: 99%
“…They also demonstrated that the efficacy of the MLP network is dependent on the nonlinearity of the S-DES internal s-boxes. Previous revolutionary papers on S-DES or other simplified ciphers include [15], [16], [17], or [18]. In 2002, an unprecedented incident occurred when a public-key approach based on neural networks was hacked using evolutionary algorithms [22].…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, the cyclic neural network (RNN) is used to find the path by minimizing the network cost function in the differential operation graph of the block cipher. In 2010, Alallayah et al [3][4][5] performed neural network-based cryptanalysis on classical cryptography, sequence ciphers, and simplified DES (SDES). They regard cryptanalysis as a black box problem, using neural networks as an ideal tool for identifying black boxes, combining system identification technology with adaptive system technology, and constructing a neuroidentifier that simulates the target cryptosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The neural output is compared with the plaintext, and performance error indicators are established for analyzing the data to improve efficiency. In 2014, Danziger et al [9] used the method in [5] to find out the mapping relationship between plaintext, ciphertext, and key in SDES. When experiments are performed using 102,400 sample data, the keys of the first, second, and fifth bits of the 10-bit key can be obtained; when the number of samples is reduced to 2000, the keys of the first and second bits can be obtained.…”
Section: Introductionmentioning
confidence: 99%